Evaluation of myocardial work in patients with resistant arterial hypertension. Issue 11 (10th October 2022) - de Andrade Hygidio, Daniel; Le Bihan, David; Batista Souza, Jonathan; Bellio de Mattos Barretto, Rodrigo; Mathias, Wilson; Gonçalves de Sousa, Marcio
Abstract: Aims: Individuals with resistant arterial hypertension are particularly at risk of developing target organ damage and cardiovascular events. The advanced echocardiography technique called myocardial work (MW), through the analysis of the left ventricular pressure‐strain loop, is among the possibilities for evaluating these individuals. Our study was designed to describe the behavior of MW indices in individuals with resistant arterial hypertension (RH), controlled hypertension (CH), and normal arterial pressure (N). Methods and Results: Seventy‐one patients underwent Ambulatory Blood Pressure Monitoring (ABPM) and were characterized into three groups after a medical consult: RH (subjects with hypertension on four or more antihypertensive medications despite having controlled blood pressure); CH (subjects with hypertension on up to two antihypertensive medications); and N (individuals with normal ABPM; not using any medications). Echocardiographic analysis was performed using the Vivid E95 ultrasound system and blood pressure was measured at the time of the examination and subsequently used to determine myocardial work indices. RH demonstrated lower global work efficiency (GWE, mean = .95%; p  = .005) and higher global wasted work (GWW, mean = 114 mm Hg%; p  = .011) compared to other groups. Left ventricular mass measured by three‐dimensional echocardiography, systolic wall stress, relative wall thickness and peak systolic dispersion were inversely correlated to GWE. No difference was observed between CH and N groups regarding MW indices. On multivariate analysis, only systolic wall stress remained as an independent predictor of GWE, when controlled by 3D mass index, relative wall thickness, peak systolic dispersion, and the hypertension group. Conclusion: Individuals with resistant hypertension have lower global work efficiency and higher global wasted work, compared to individuals with controlled hypertension and without arterial hypertension.